COMPARISON BETWEEN EFFICACY OF PALONOSETRON AND ONDANSETRON IN POSTOPERATIVE NAUSEA AND VOMITING IN MIDDLE EAR SURGERY: A RANDOMIZED DOUBLE BLIND STUDY. - NUPUR CHAKRAVARTY; SHIV KUMAR RAGHUWANSHI (International Journal of Pharma and Bio Sciences, 2013)
Postoperative nausea and vomiting (PONV) is a common complication in patients after middle ear surgeries conducted under general anaesthesia. This prospective, randomized, double blind study study compares the effects of anti emetic drugs palonosetron and ondansetron on postoperative nausea and vomiting in patients undergoing middle ear surgeries under general anaesthesia. METHOD: Sixty ASA grade I-II patients between 20-50 years scheduled for tympanomastoid surgery under general anaesthesia were administered Ondansetron 4 mg (Group O) and Palonosetron 0.075 mg (group P) intravenously before induction of anaesthesia. Postoperative study period was divided into early (0-6 hours) and late (6-24 hours) period. The incidence of of nausea, vomiting and requirement of rescue antiemetic in patients of both groups was studied. PONV was evaluated on a four point scale. Statistical analysis was done using appropriate tests. Results are described as numbers (%) and mean+/- SD. p value <0.05 was taken to be significant. RESULTS: No statistical significance could be detected between mean PONV scores of group P and group O (0.930 vs 1.68) during early recovery phase. Number of patients showing complete response to drug in both groups were comparable in the first 6 hours (p>0.05), but were significantly more in group P between 6-24 hours (p<0.05). Number of patients having nausea and retching was significantly less in group P in the delayed recovery period (6-24 hrs). CONCLUSION: Intravenous palonosetron 0.075 mg has a comparable but prolonged prophylactic profile in preventing nausea and retching after middle ear surgery under general anaesthesia when compared to Ondansetron .